2020
DOI: 10.3389/fpls.2020.590347
|View full text |Cite
|
Sign up to set email alerts
|

Birds Perceive More Intraspecific Color Variation in Bird-Pollinated Than Bee-Pollinated Flowers

Abstract: Pollinator-mediated selection is expected to constrain floral color variation within plant populations. Here, we test for patterns of constraint on floral color variation in 38 bee- and/or hummingbird-pollinated plant species from Colorado, United States. We collected reflectance spectra for at least 15 individuals in each of 1–3 populations of each species (total 78 populations) and modeled perceived color variation in both bee and bird visual spaces. We hypothesized that bees would perceive less intraspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…The role of pelargonidins in bird-pollinated flowers was previously reported in species of the Solanaceae and Gesnerioideae Smith, 2016, 2018;Ogutcen et al, 2020). Although birds do not show preferences for a particular colour, they have an excellent colour discrimination (Lunau et al, 2011;Stoddard et al, 2020;Whitney et al, 2020). Our results suggest that both carotenoids and pelargonidins pigments generate a higher conspicuousness to birds than other pigment groups, which would favour their accumulation in flowers of bird-pollinated species.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The role of pelargonidins in bird-pollinated flowers was previously reported in species of the Solanaceae and Gesnerioideae Smith, 2016, 2018;Ogutcen et al, 2020). Although birds do not show preferences for a particular colour, they have an excellent colour discrimination (Lunau et al, 2011;Stoddard et al, 2020;Whitney et al, 2020). Our results suggest that both carotenoids and pelargonidins pigments generate a higher conspicuousness to birds than other pigment groups, which would favour their accumulation in flowers of bird-pollinated species.…”
Section: Discussionsupporting
confidence: 77%
“…As the previous ones, this model also allows to measure perceived chromatic differences among stimuli (Endler and Mielke, 2005;Stoddard and Prum, 2008;Camargo et al, 2019). A considerable number of studies show that functional groups of pollinators can perceive differently the same flower colour (e.g., Ohashi et al, 2015;Bergamo et al, 2018;Whitney et al, 2020). In fact, it has been demonstrated that flower colours have evolved in different regions of the world to match the visual capabilities and preferences of local pollinator fauna (Burd et al, 2014;Shrestha et al, 2016;Camargo et al, 2019;Coimbra et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…Predictions from RN depend on the precise value of its various parameters, and in particular, on the magnitude of noise coefficients (e i ) assigned to the different photoreceptors (Lind and Kelber, 2009). In spite of the wide use of the RN model for answering questions regarding avian visual ecology such as: discrimination of parasitic eggs by hosts (Hanley et al, 2019), camouflage by female birds (Cain et al, 2019), and perceived flower colour variation by pollinating species at population level (Whitney et al, 2020); to cite just a few recent examples, no noise measurement data currently exist for any avian species. In most cases, the unknown but essential noise values are derived from applying theoretical assumptions of signal detection theory to photoreceptor density data (Vorobyev and Osorio, 1998), although it still remains unclear how neural processing by the brain may affect these assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Of these types of pigments, anthocyanins are most commonly associated with flower color polymorphisms (Sapir et al, 2021). Indeed, many species for which flower color variation was reported (Frey, 2004;Rakosy et al, 2012;Renoult et al, 2013;Sletvold et al, 2016;Dormont et al, 2019;Paine et al, 2019;Streinzer et al, 2019;Gómez et al, 2020;Whitney et al, 2020) have blue, pink or purple colors that are commonly due to anthocyanin pigments. It would be interesting to know, for these species, how standing variation in pigmentation relates to the flower's conspicuousness to their pollinators.…”
Section: The Amount Of Pigment and Perspectives For Future Studies On Flower Colormentioning
confidence: 99%
“…Something to consider is that the perceived flower color variation probably differs across pollinators. Whitney et al (2020), for example, recently showed that for the same set of flowers, birds perceive more intraspecific variation than bees. It is known that different pollinators select for different flower colors (hues) owing to variation in spectral sensitivity and/or color preferences (Lunau et al, 2011;Shrestha et al, 2013;, but pollinators may also impose different selective pressures on the degree of variation around a certain hue.…”
Section: The Amount Of Pigment and Perspectives For Future Studies On Flower Colormentioning
confidence: 99%